PENGARUH DOSIS KOMPOS KULIT BUAH KAKAO DAN INTERVAL PENYIRAMAN PADA BIBIT KELAPA SAWIT(Elaeis guineensisJacq.) DI PEMBIBITAN UTAMA - Boy Novendi Sinaga; Ardian '; Edison Anom (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research is to know the influence compost dosage interaction on Cocoa Fruit Peel and Watering Interval for the growth of oil palm Seed (Elaeis guineensisJacq)  in the primary nursery.  The research has done in conservatory of Agriculture faculty, Riau University, Bina Widya Street Km 12,5 Simpang Baru, Tampan Pekanbaru. This research was held 4 months, starting from September –December 2014 by using experiment design with Completely Randomize Design ( CRD) factorial, by 2 factors treatment and the result become 9 treatments. Every treatment was repeated 3 times, and retrieved 27 units of experiment. There were 2 seeds in every units of treatments, and the total were 54 seeds. The parameter were observed is a high added of seed growth, stem leave diameter,the root header  ratio and the seedling dry weight. The obtaining data were analyzed by using ANOVA test and continued with further DNMRT on 5% level. The research result showed that Dosage composting of cocoa fruit peel, gives the best effect of seed growth, the number of stem leaves, the stem diameter, the root header ratio and the seedling dry weight. Watering interval gives the best effect of seed growth, the number of leaves, the stem diameter,the root header ratio and the seedling dry weight. The growth of palm oil seed was best with a dose of 200 g/polybag or equivalent with 50 tons /ha with watering interval one times on two days. Keywords : Palm oil, Cocoa fruit peel compost and interval watering.